Fracture criterion for predicting surface cracking of Ti40 alloy in hot forming processes - 张学敏 曾卫东 舒滢 周义刚 赵永庆 吴欢 俞汉清 (Transactions of Nonferrous Metals Society of China, 2009)
Hot compression tests were conducted on Ti40 burn resistant titanium alloy in the temperature range of 900-1 100℃ and strain rate range of 0.01-10 s^-1 to investigate its fracture behavior and critical fracture conditions in hot forming. It was observed that the failure of Ti40 alloy is attributed to longitudinal surface cracking due to severe oxidation of element V and the secondary tensile stresses. The critical fracture strain increases with increasing temperature and decreasing strain rate. From these observations and parallel FEM simulations, it was concluded that the critical fracture strain is a function of a single argument Zener-Hollomon parameter, and there is a linear relationship between them. An Oyane criterion successfully predicted the location of crack initiation. The critical fracture values also exhibit a liner relationship with lnZ. Based on these results, a new fracture criterion of Ti40 alloy based on Zener-Hollomon parameter was established.